Comparison of Performance Rot13 and Caesar Cipher Method for Registration Database of Vessels Berthed at P.T. Samudera Indonesia - Risman Risman (International Journal of Basic and Applied Science, 2021)
Database security is a very important aspect of an information system. A general information is onlyintended for certain groups. Therefore, it is very important for a company to prevent database leakage sothat the information contained in it does not fall to unauthorized people. Cryptographic technique is an alternative solution that can be used in database security. One way to maintain the security of the database is to use encryption techniques. The method used to secure the database is encryption using the ROTI3 and Caesar Cipher methods. Both of these methods have advantages in processing speed. For thisreason, the author will compare the use of the two algorithms above in terms of the encryption and decryption process time